Microbial diversity in soils suppressive to Fusarium diseases - Todorović, Irena; Moënne-Loccoz, Yvan; Raičević, Vera; Jovičić-Petrović, Jelena; Muller, Daniel (Frontiers in Plant Science, 2023)
Fusarium species are cosmopolitan soil phytopathogens from the division Ascomycota, which produce mycotoxins and cause significant economic losses of crop plants. However, soils suppressive to Fusarium diseases are known to occur, and recent knowledge on microbial diversity in these soils has shed new lights on phytoprotection effects. In this review, we synthesize current knowledge on soils suppressive to Fusarium diseases and the role of their rhizosphere microbiota in phytoprotection. This is an important issue, as disease does not develop significantly in suppressive soils even though pathogenic Fusarium and susceptible host plant are present, and weather conditions are suitable for disease. Soils suppressive to Fusarium diseases are documented in different regions of the world. They contain biocontrol microorganisms, which act by inducing plants' resistance to the pathogen, competing with or inhibiting the pathogen, or parasitizing the pathogen.In particular, some of the Bacillus, Pseudomonas, Paenibacillus and Streptomyces species are involved in plant protection from Fusarium diseases. Besides specific bacterial populations involved in disease suppression, next-generation sequencing and ecological networks have largely contributed to the understanding of microbial communities in soils suppressive or not to Fusarium diseases, revealing different microbial community patterns and differences for a notable number of taxa, according to the Fusarium pathosystem, the host plant and the origin of the soil. Agricultural practices can significantly influence soil suppressiveness to Fusarium disease by influencing soil microbiota ecology. Research on microbial modes of action and diversity in suppressive soils should help guide the development of effective farming practices for Fusarium disease management in sustainable agriculture.